The influence of differential leadership and proactive personality on employee in-role performance: An integrated model - Chen, Sze-Ting; Haga, Kai Yin Allison (Frontiers in Psychology, 2022)
Purpose: Differential leadership does not necessarily bring only negative effects, but may also become an incentive management strategy. This study explores whether outsiders of uniquely Chinese culture can actively become insiders through proactive personality traits, or whether they can actively approach resource controllers to remove work situation obstacles to enhance their work performance. Methodology: A stratified random sampling method was used. The sample objects were medical staff from hospitals in the six urban districts of Beijing, including below, grade II, grade III and above. A total of 900 online questionnaires were distributed. Finally, 524 valid questionnaires were recovered. Main Findings: The results show that differential leadership, which is favoritism towards insiders and disliked against outsiders, can show different changes in employees’ sense of organizational justice and in-role performance. Meanwhile, by introducing proactive personality as an independent variable that also acts as a moderator, our study confirms that under differential leadership, employees with proactive personality can actively improve situational barriers and have better work performance. Implications/Applications: Our research can provide managers with the following advice: First, it is better not only to look at the relationship, but also to understand the employee's personality characteristics, whether it is a superficial or deep role at work, in order to reduce turnover rate or to raise productivity. Second, it is important to teach employees to serve sincerely from the customer's point of view, rather than relying on the outward appearance of friendliness. Novelty/Originality: This paper contributes to the theory of proactive personality, emotional labor, and differential leadership. Contrary to previous studies, proactive personality rarely acts as both a distractor and a predictor at the same time. Also, insiders favored by leaders do not perform better at work.